Role of Color and Typography in Determining Brand Personality - Jain, Kokil; Pasricha, Diksha (Indian Journal of Marketing, 2017)
Purpose : This research explored the effect of typography and color on consumer's perceptions of brand personality. Drawing on the sematic influence of type font framework, three independent experimental studies involving two types of typographical fonts - Pepita MT and Logan were conducted. Also, four primary colors were introduced in the study to explore the effect of color independently on brand personality and interaction of the same with typography and their synergistic effect on brand personality. Design/Methodology/Approach : A hypothetical brand name â€œTidameâ€ was introduced in the study. The brand name was invented and had no previous existence in the market place. All the hypothesized dimensions were tested on two different product categories - fashion apparels and glue stick. The Study 1 explored the effect of type of typography on brand personality. The Study 2 examined the effect of color on brand personality. The Study 3 probed how color and typography, when taken together, affected brand personality. A random sample of around 200 individuals was selected. Out of the received responses, 155 were complete responses. They were further analyzed statistically using SPSS 20. This research was carried out in between December 2015 and February 2016. Findings : Typography of the brand name, when independently taken, did not show any significant effect on brand personality. Color was a determining factor in brand personality in both the product categories. Also, the interactive effect of font type and color in forming perceptions of brand personality, especially in the case of fashion apparel, was evidently concluded. Research Limitations/Implications: The limitation of this research was the small size of the sample restricted to just one region of India. Practical Implications: The most important practical viewpoint of the study is that it provides the managers an understanding of color and typography in forming perceptions about brand personality. It also gave an insight into the role of product category associations in moderating the effect of color and type font on brand personality. Originality/Value : This is perhaps the first study in India that attempted to measure the interactive role of color, type font, and product category in determining the personality of a brand.